Prikaz Slovenije v osnovnošolskih učbenikih geografije Evrope na območju nekdanje Jugoslavije - Senegačnik, Jurij (Geografski vestnik, 2003)
The contribution first treats the content presentation of Slovenia in four selected textbooks to which we applied an adapted method of quantitative and qualitative content analysis. In all of the textbooks, a combined approach is evident that is a combination of general geographical regional geography of Europe and region regional geography of Europe. In each textbook, a special subchapter is devoted to Slovenia, the main subject of our analysis. Proportionally, above-average attention is devoted to our country from the quantitative viewpoint; however, quantity here does not necessarily mean quality. The quantity of geographical names from Slovenia is in some textbooks too large, and there are many errors as well. An analysis of twenty-six selected code units showed above all that the sociogeographical presentation of Slovenia is outdated and in places misleading.
Keywords: Slovenia; Slovenija; regional geography; regionalna geografija; učni programi; učbeniki za osnovne šole